Literatura e história: diálogos na sala de aula - Engel, Odilse Grasselli (My University, 2014)
Interdisciplinary dialogue approach proposal inserted between History and Literature, in order to discuss how a literary text can be used in History classes of High School. A research into the underneath ideology at educational books and their acritical assimilation by readerstudents. Checking and analysing the presence or not of Literature in High School educational text-books, as well as the approach of historical facts that happened in Rio Grande do Sul, like Revolução Farroupilha and Italian Immigration. Giving emphasis to the Educational role and having in mind, as a study object, the novel A Cocanha by José Clemente Pozenato, it looks for touching the teaching practice of History and allows to realize that literary fiction is an effective instrument(way) in teaching-learning process.
Proposta de diálogo interdisciplinar entre Literatura e História, com o propósito de discutir de que forma o texto literário pode ser aproveitado nas aulas de História do Ensino Médio. Investigação da ideologia subjacente a livros didáticos do Ensino Médio e sua assimilação acrítica pelos alunos-leitores. Verificação e análise da presença ou não da Literatura em manuais didáticos do Ensino Médio, bem como da abordagem de fatos históricos ocorridos no Rio Grande do Sul, como a Revolução Farroupilha e a imigração italiana. Com ênfase no papel da educação e tendo como objeto de estudo o romance A Cocanha, de José Clemente Pozenato, procura sensibilizar a prática docente da área de História para a percepção de que a ficção literária constitui um instrumento eficaz no processo de ensino-aprendizagem.
Keywords: Ensino e aprendizagem na sala de aula; Literatura e história; Imigração italiana; Ensino-aprendizagem; Interdisciplinaridade; A Cocanha (Obra literária, 2000); Livros didáticos; Ensino médio; History; Literature; Italian immigration; Teaching-learning practice; Interdisciplinary approach